COST UTILITY ANALYSIS PADA PASIEN DIABETES MELLITUS TIPE 2: INTEGRASI GULA DARAH, KOMORBIDITAS, BIAYA DAN KUALITAS HIDUP DALAM PENGAMBILAN KEPUTUSAN KLINIS - Ilahi, Fitrah Shafran; Nordin; Faqih, Muhammad; Yumassik, Abdul Mahmud; Mellyani H.S, Ananda (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
Type 2 Diabetes Mellitus (T2DM) is one of the most prevalent chronic diseases in Indonesia and imposes a significant burden on healthcare costs. This study aimed to perform a Cost Utility Analysis (CUA) among T2DM patients by integrating blood glucose levels, comorbidities, direct medical costs, and quality of life. The research applied a cross-sectional design with prospective data collection using a convenience sampling technique. Quality of life was measured using the EQ-5D-5L questionnaire, while blood glucose levels, comorbidities, and direct medical costs were obtained from hospital medical records. Data analysis included descriptive statistics, Chi-Square tests, Logistic Regression analysis, and calculation of the utility index. The results showed that 38% of patients had good quality of life and 62% had poor quality of life, with an average utility index score of 0.5175. Random blood glucose levels of ≥200 mg/dL were found in 56% of respondents, while 44% had levels <200 mg/dL. Comorbidities were present in 52% of patients, while 48% had none. The median direct medical cost was IDR 425,500, with 62% categorized as high-cost and 38% as low-cost. Bivariate analysis revealed significant relationships between comorbidities, blood glucose levels, and direct medical costs with quality of life (p < 0.05). However, multivariate analysis showed that only blood glucose levels remained significant (p = 0.006). In conclusion, the overall quality of life of T2DM patients was generally poor, and blood glucose control was identified as the most influential independent factor affecting quality of life.